Two pesticides blacklisted - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On 2 August 1999, the United States Environmental Protection Agency (EPA) imposed severe restrictions on two widely used pesticides: methyl parathion and azynphos methyl. These organophosporous substances can no longer be used on market garden or...